ANALISIS TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE RGEC (RISK, PROFILE, GOOD CORPORATE GOVERNANCE, EARNING, AND CAPITAL) PADA PT. BANK PERMATA Tbk. PERIODE 2019-2021 - Simatupang, Eva Malina; L. Tobing, Vargo Christian; Banjarnahor, Haposan (JURNAL AKUNTANSI BARELANG, 2024)
The purpose was to find out the soundness of the bank PT Bank Permata Tbk for the period 2019-2021 using the RGEC method. The population is the financial statements of PT Bank Permata Tbk and the samples are the statement of financial position (balance sheet), income statement, and notes to the financial statements of PT Bank Permata Tbk for the 2019-2021 period. The type of data used is quantitative data with secondary data, using data collection techniques, namely documentation techniques through the website of Bank Permata. The data processing technique used is a descriptive technique using the RGEC method. Based on the results of data processing, it can be concluded that PT Bank Permata Tbk in 2019 to 2021 obtained a composite rating (PK) 1 in the very healthy category. This reflects the condition of the bank which is generally very healthy, so it is considered very capable of dealing with significant negative influences and changes in business conditions and other external factors.